Coping with Stressors by Drawing on Social Supports: The Experiences of Adolescent Syrian Refugees in Canada - Salam, Zoha; Gajaria, Amy; Wahoush, Olive; Nouvet, Elysee (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2022)
This study explores how teenage Syrian refugees use their social networks to cope with stressors. Through interviews with nine youth aged 16 to 18 living in Ontario, Canada, stressors related to pre- and post-migration emerged. Family, peers, school staff, and organizations were identified as social networks, each having unique reasons why they were selected. Coping was categorized as individualistic or collectivistic. Teenage Syrian refugees draw upon social resources to navigate situations they are faced with, and cultural values influence the stress and coping process. Findings have implications for mental health care providers and policy-makers focused on migrant resettlement.